Association between intraoperative steroid and postoperative mortality in patients undergoing craniotomy for brain tumor - He, Jialing; He, Shuanghong; Zhang, Yu; Tian, Yixin; Hao, Pengfei; Li, Tiangui; Xiao, Yangchun; Peng, Liyuan; Feng, Yuning; Cheng, Xin; Deng, Haidong; Wang, Peng; et al. (Frontiers in Neurology, 2023)
BACKGROUND: Despite the widespread use of intraoperative steroid in various neurological surgeries to reduce cerebral edema and other adverse symptoms, there is sparse evidence in the literature for the optimal and safe usage of intraoperative steroid administration in patients undergoing craniotomy for brain tumor. We aimed to investigate the effects of intraoperative steroid administration on postoperative 30-day mortality in patients undergoing craniotomy for brain tumor. METHODS: Adult patients who underwent craniotomy for brain tumor between January 2011 to January 2020 were included at West China Hospital, Sichuan University in this retrospective cohort study. Stratified analysis based on type of brain tumor was conducted to explore the potential interaction. RESULTS: This study included 8,663 patients undergoing craniotomy for brain tumor. In patients with benign brain tumors, intraoperative administration of steroids was associated with higher risk of postoperative 30-day (adjusted OR 1.98, 95% CI 1.09-3.57). However, in patients with malignant brain tumors, no significant association was found between intraoperative steroid administration and postoperative 30-day mortality (adjusted OR 0.86, 95% CI 0.55-1.35). Additionally, administration of intraoperative steroids was not associated with acute kidney injury (adjusted OR 1.11, 95% CI 0.71-1.73), pneumonia (adjusted OR 0.89, 95% CI 0.74-1.07), surgical site infection (adjusted OR 0.78, 95% CI 0.50-1.22) with 30 days, and stress hyperglycemia (adjusted OR 1.05, 95% CI 0.81-1.38) with 24 hours after craniotomy for brain tumor. CONCLUSIONS: In patients undergoing craniotomy for benign brain tumor, intraoperative steroids were associated with 30-day mortality, but this association was not significant in patients with malignant brain tumor.